Twice‐Daily Doravirine Overcomes the Interaction Effect from Once‐Weekly Rifapentine and Isoniazid in Healthy Volunteers. Issue 6 (29th May 2020) - Lam, Edwin; Schaefer, Joseph; Zheng, Richard; Zhan, Tingting; Kraft, Walter K.
Abstract : Doravirine (DOR) is a non‐nucleoside reverse transcriptase inhibitor indicated for the treatment of HIV‐1. Its use in combination with rifapentine (RPT), an antituberculosis (TB) antibiotic, may reduce the exposure of DOR compromising viral suppression in those living with HIV‐1 co‐infected with TB. We conducted a prospective, phase I, open label, two‐period, fixed sequence, drug interaction study to evaluate the effect of once‐weekly RPT and isoniazid (INH) on the pharmacokinetics (PKs) of DOR in healthy volunteers. DOR 100 mg was administered alone twice‐daily for 4 days in period 1. In period 2, once‐weekly RPT + INH were co‐administered with multiple doses of DOR 100 mg twice‐daily for study days 7, 14, and 21. Plasma was obtained for DOR PKs when given alone and co‐administered with RPT + INH. Eleven healthy volunteers enrolled and completed the study. The geometric mean ratios and 90% confidence intervals for DOR area under the concentration‐time curve from zero to 12 hours (AUC0–12 ) and C12 in the presence of RPT + INH compared with DOR alone were 0.71 (0.60–0.85) and 0.69 (0.54–0.89), respectively. Although exposures were moderately reduced in the presence of RPT + INH, trough DOR values were within the concentration range associated with virological suppression. These results demonstrate that a modest decrease in DOR exposure would unlikely be clinically relevant in a virally suppressed patient co‐administered once‐weekly RPT + INH.